(3JQcjH GdCOhjI GdbdHjIs - (3GdfLjH GdSeQbfOj , eMeO Hf Ydj Hf YeQ GdSeQbfOj, fLjH GdOjf CHh MGeO,J (B619 (3g` s
(3ChdgG (B:s
(3GdCOhjI GdbdHjI GdeSJYedI ai GdeaQMGJ JSJYed Ydi CfMGA ef GdJQcjH , dCfgG JSJYed JGQI dJSNjf GdbdH hGdQhM , hJGQI dJHQjOgeG s
(3BNQgG (B:s
(3JNdW GdMGQI eKd GdYhO hGdYfHQ HGdHGQOI eKd GdcGahQ GdUfOd , hEf CQjO JZdjH EMOi GdcjajGJ Ch HYV NhGUgG hGaYGdgG jcKQ ai GdeQcH eGdI Jdc GdNGUjI , hPdc GdaYd GdeWdhH hGdcjajI GdeWdhHI s
(3Vef eLehY s
(3GfXQg eY OaY GdSehe Qbe (B" 467"s
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B280 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B31s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfi (B- (3U (B53 s
Keywords: (3GdWHs